The Effect of Promotional and Prices on Consumer Satisfaction as Mediated by Service Quality at Akela Meubel, Medan City - Erizal Erizal; Elfitra Desy Surya (International Journal of Economics and Management Sciences, 2025)
This study aims to examine and analyze the impact of promotions and prices on customer satisfaction, mediated by service quality in Medan City. The research is quantitative in nature, using an accidental sampling technique. Data collection was done through questionnaires and interviews. Data analysis was performed using SMART PLS. The population consisted of 50 respondents, all of whom were included as the research sample. The findings reveal that promotion has a positive and significant effect on service quality in Medan furniture stores. Price also positively and significantly impacts service quality at Akela Meubel in Medan. Promotions positively and significantly influence customer satisfaction at Akela Meubel, while price has a positive and significant effect on customer satisfaction in Medan furniture. Furthermore, promotion positively and significantly affects customer satisfaction at Akela Meubel in Medan through service quality, and price positively impacts satisfaction through service quality at Medan furniture.